Characterization of visual symptoms and growth of australian cedar seedlings under nutritional deficiencies - Batista, Raquel Oliveira; Furtini Neto, Antonio Eduardo; Hickmann, Clério; Duarte, Rômulo Fredson; Amaral, Douglas Carvalho; Araújo, Breno Henrique; de Jesús Lacerda, Julian Junio; Deccetti, Soami Fernanda Caio (Agrarian, 2014)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Australian cedar is an exotic species adapted to soil and climatic conditions of Brazil. This study aimed to characterize the symptoms of nutritional deficiencies and their effect on cloned australian cedar seedling growth via the missing element technique. We used seedlings of two clones of australian cedar (MB and XB) and the experimental design was completely randomized with eight treatments consisting of: a complete nutrient solution, omitting the joint solution of macronutrients (multiple deficiency - MD) and solutions with omission of N, P, K, Ca, Mg and S. Nutrient deficiency symptoms were described and photographed. Characteristics were evaluated: height, stem diameter, aerial part dry mass (APDM), root dry mass (RDM), and RDM/APDM ratio. In summary, with omission of N, the plants showed reduced growth and chlorosis of older leaves, with later evolution to younger leaves. These symptoms were similar to those presented by the plants that did not receive nutrients (DM). Moreover, plants with S deficiency showed chlorosis on younger leaves. With the omission of P, was observed only a slight coloration of leaves to blue-green, in the absence of K, chlorosis followed by necrosis with particularities for each clone, and interveinal chlorosis on deficient Mg plants. In general, the N, Ca and S omissions limited the growth of the specie. The decreases in dry matter production yield due to nutrient omissions occur in the following order: Ca> K> Mg> S> N for clone MB and K> Mg> Ca> S> N for clone XB. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>